1)x=5 => 3*5 +7y=11 =>15+7y=11=>7y=11-15=>7y=-4=>y= - 4/7
2)x=4y => 3*4y + 5y -15 =0=> 17y = 15 => y =15/17
x = 4* (15/17) = 60/17
a)9x+11y = 15
7x+11y = 19 | (-1)
amplifici a doua ecuatie cu -1 si sitemul devine
9x+11y=15
-7x-11y=-19
ecuatia 1 - ecuatia 2
9x-7x+11y-11y=15-19 => 2x = - 4 => x = - 2
9*(-2) + 11y = 15 => -18 +11y = 15 => 11y = 15 + 18 => 11y=33 => y =3
b)4x +y = 7 | (-2)
9x + 2y = 62
amplifici prima ecuatie cu -2
-8x - 2y = -14
9x+2y=62
ecuatia 1 - ecuatia 2
-8x + 9x -2y+2y= -14 + 62=> x = 48
4 * 48 + y = 7
y = 7 - 4*48
y = 7 - 192
y = -185